Female Platelets Have Distinct Functional Activity Compared to Male Platelets: Implications in Transfusion Practice and Treatment of Trauma-Induced Coagulopathy - Coleman, Julia R (J Trauma Acute Care Surg, 2019)
BACKGROUND: Females are hypercoagulable and have survival benefit in trauma-induced coagulopathy (TIC). The mechanism for this sex-specific hypercoagulability is unknown. Platelets and platelet function are central in providing hemostatic potential and are the largest contributor to clot strength. Ligands (adenosine diphosphate [ADP] and platelet activating factor [PAF]) bind distinct platelet receptors to potentiate activation and aggregation. We hypothesize that female platelets have a differential response to ADP and PAF, resulting in greater aggregation and activation compared to males, and that estradiol pre-treatment of male or female platelets enhances this activity. METHODS: Platelets were collected from healthy volunteers: pre/post-menopausal females (≤54 years old,>54 years old) and similarly aged males. Platelet aggregometry and flow cytometry (fibrinogen binding capacity) were examined. After treatment with ADP or PAF, platelet aggregation was assessed with Chronolog and activation assessed by CD41 receptor surface expression using flow cytometry. Aggregation and activation were again assessed after platelet pre-treatment with estradiol. RESULTS: Healthy volunteers included 12 premenopausal and 13 postmenopausal females and 18 similarly aged males. Female platelets (combined pre- and postmenopausal) had increased aggregation with ADP stimulation, as compared to male platelets. Male and female platelets had differential fibrinogen receptor expression, with female platelets (combined pre- and postmenopausal) demonstrating robust activation with ADP versus male platelets with PAF. In the presence of estradiol incubation, male platelets’ activation with PAF approximated that of females (combined pre- and postmenopausal) and activation with PAF was enhanced in both male and female platelets. CONCLUSIONS: Male and female platelets have differential response to stimuli, suggesting sex-dependent signaling and cellular activation. Female platelets have both increased aggregation and activation potential, and estradiol pre-treatment feminizes male platelets to approximate female platelet activation with PAF. These findings offer potential explanation for sex-based differences in hemostatic potential in TIC and question whether donor sex of transfused platelets should be considered in resuscitation. Estradiol may also serve as a novel therapeutic adjunct in TIC. LEVEL OF EVIDENCE: This is a basic science project and as such, does not require a level of evidence. STUDY TYPE: Original Article.